2021
DOI: 10.1017/cjn.2021.180
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and Head/Eyes/Ears/Nose/Throat Manifestations of COVID-19: A Systematic Review and Meta-Analysis

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 150 publications
(182 reference statements)
4
16
1
Order By: Relevance
“…In our study, patients with both AIS and COVID-19 had significantly higher in-hospital mortality at 16.9%, which was lower than the mortality of 20% to 63.6% documented in the literature yet higher than those with COVID-19 without AIS at 13.1% [ 5 , 9 , 10 ]. When further mortality analysis was performed, which evaluated gender, race, and age, it was found that gender and race have a significant role in mortality outcomes in COVID-19-positive AIS patients, as discussed above.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…In our study, patients with both AIS and COVID-19 had significantly higher in-hospital mortality at 16.9%, which was lower than the mortality of 20% to 63.6% documented in the literature yet higher than those with COVID-19 without AIS at 13.1% [ 5 , 9 , 10 ]. When further mortality analysis was performed, which evaluated gender, race, and age, it was found that gender and race have a significant role in mortality outcomes in COVID-19-positive AIS patients, as discussed above.…”
Section: Discussioncontrasting
confidence: 55%
“…Neurological complications have been documented in approximately 36.4% of COVID-19 patients, and roughly 28.2% had severe central nervous system (CNS) injuries, contributing to worse morbidity and mortality [ 4 ]. Known neurological complications include acute ischemic stroke (AIS), neuropsychiatric symptoms, encephalopathy, seizures, myopathies, and polyradiculoneuropathies [ 5 ]. COVID-19 infection is associated with worse outcomes in AIS patients [ 6 , 7 ]; however, large-scale studies evaluating AIS outcomes with COVID-19 infection are limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seizures 1-4.05% [29,30] Encephalopathy 7-23.5% [29,30] Ischemic stroke 1.3-3% [31][32][33] Hemorrhagic stroke 0.4-0.6% [32,33] Olfactory dysfunction 19-55% [29,30,34] Gustatory dysfunction 21-41% [29,30,34,35] Headache 13-47.1% [29,30,36,37] Fatigue 32-37.8% [29,30,36] Peripheral Neuropathy 1% [30] Cognitive impairment 2% [30] Many COVID-19-associated neurological symptoms persist long after the respiratory process passes. One year after COVID-19 infection, persistent neurological sequelae were reported in 12% of patients; symptoms included fatigue, concentration difficulties, forgetfulness, sleep disturbances, limb weakness, and headache in descending order of prevalence [20].…”
Section: Pooled Prevalencementioning
confidence: 99%